PRESENTASI DIRI PEKERJA MILENIAL SKK MIGAS - PETROCHINA INTERNATIONAL JABUNG LTD. JAKARTA DI MEDIA SOSIAL - Melita, Yerah; Waruwu, Aris (Jurnal Insani, 2023)
The phenomenon of millennial workers' self-presentation on social media is still unclear or questionable. Millennial workers are worried about their unclear employment status. Their employment status is still as contract workers. They are still very at risk due to their employee status. Indications regarding their performance assessment still need to be reviewed again by superiors and management. One way they do this is by presenting themselves on social media. Millennial workers did not waste this opportunity, they started presenting themselves with various self-presentation content. This research examines in detail the self-presentation of millennial workers of SKK Migas - PetroChina International Jabung Ltd. Jakarta on social media. This research aims to find out and provide an overview of the self-presentation of millennial workers at SKK Migas PetroChina International Jabung Ltd, Jakarta, which refers to Dramaturgical Theory. To obtain answers from the research, researchers used qualitative research methods with 5 (five) informants using purposive sampling techniques. The data collection techniques used were observation, in- depth direct interviews with informants, and creating documentation in the form of notes from interviews with informants as well as photos of millennial workers' self-presentation. The results of this research show that dramaturgy in millennial workers' self-presentation is carried out with full awareness and strong consideration in selecting and sorting the content of self-presentation.